2023
DOI: 10.3390/network3010010
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Applied to LoRaWAN Network for Improving Fingerprint Localization Accuracy in Dense Urban Areas

Abstract: In the area of low-power wireless networks, one technology that many researchers are focusing on relates to positioning methods such as fingerprinting in densely populated urban areas. This work presents an experimental study aimed at quantifying mean location estimation error in populated areas. Using a dataset provided by the University of Antwerp, a neural network was implemented with the aim of providing end-device location. In this way, we were able to measure the mean localization error in areas of high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It localizes using the RSSI data and the trilateration approach. Perkovic et al [16] found the localization and the precise RSSI values published to the Message Queuing Telemetry Transport (MQTT) server of the remote location using an ML method. We assess and explain the localization inaccuracy between the predicted and actual.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It localizes using the RSSI data and the trilateration approach. Perkovic et al [16] found the localization and the precise RSSI values published to the Message Queuing Telemetry Transport (MQTT) server of the remote location using an ML method. We assess and explain the localization inaccuracy between the predicted and actual.…”
Section: Related Workmentioning
confidence: 99%
“…schedule is 93.2584 and error (m) of 674 16. for SOMs in the linear RSS model and MLP in the power RSS model.…”
mentioning
confidence: 99%
“…In addition, LoRaWAN offers features such as adaptive data rate (ADR) for efficient resource management, bi-directional communication, and strong security, making it a robust and scalable solution for IoT deployments [ 40 ]. With their long range, ultra-low power consumption, and efficient network management, LoRa and LoRaWAN are revolutionizing the IoT landscape, empowering businesses and industries with seamless connectivity and enabling innovative IoT applications across various sectors [ 41 ].…”
Section: Introductionmentioning
confidence: 99%